Well-Being as a Primary Determinant of Early Childhood Development: A Comprehensive Literature Review - Nur Laila Sari; Rusnaniah Rusnaniah; Novi Andriani Fauzi; Nurhayati Bemba; Nurlina Syam (Lembaga Riset Mutiara Akbar, 2025)
This study aims to analyze the influence of well-being on early childhood development through a comprehensive literature review. The research employed a library research method by examining national and international articles discussing dimensions of child well-being, including physical, emotional, social, cognitive, and environmental aspects. Content analysis was used to identify patterns, conceptual relationships, and the contribution of well-being to children’s holistic development. The findings indicate that well-being serves as a primary predictor of early childhood development. Emotional well-being plays a significant role in enhancing self-regulation, social competence, and emotional stability. Physical well-being—encompassing bodily growth and structured physical activity—has been shown to support motor development and cognitive functioning. In addition, the quality of the educational environment, warm teacher–child interactions, and responsive parenting at home constitute ecosystem factors that strengthen children’s well-being. Conversely, low levels of well-being are associated with behavioral problems, learning difficulties, and emotional disturbances. The study concludes that efforts to enhance children’s well-being must be carried out through a holistic and collaborative approach involving families, educators, early childhood institutions, and the broader social environment. Such integrative efforts are essential to ensure that children grow healthily, happily, and reach their optimal developmental potential.